Frequency of Acute Kidney Injury among Women Presenting with Pre-Eclampsia - Hamid Ullah, Sumaira, Muhammad Shaukat, Muhammad Abbas, Humaira Aman, Saboor Ahmed Kakar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pregnancy-related hypertension, or pre-eclampsia, is a serious risk factor for both the mother and the fetus. Acute kidney injury (AKI), one of its side effects, is a growing worry as it raises maternal morbidity and may result in long-term renal damage. Objective: To find how common AKI is among women with pre-eclampsia. Methods: This six-month cross-sectional study was carried out at Bacha Khan Medical College's Mardan Medical Complex-MTI between February and July of 2023. Non-probability consecutive sampling was used to recruit 142 pre-eclamptic women. A thorough clinical evaluation that included a history, physical examination, urinalysis, and testing for renal function was performed on each participant. KDIGO criteria were used to diagnose AKI. SPSS version 26 was used for data analysis, and descriptive statistics and, when applicable, Chi-square/Fisher's exact tests were used. Results: The frequency of AKI among pre-eclamptic women was 28.9% (n = 41). A significant association was observed between AKI and the severity of pre-eclampsia (p = 0.001), with 87.8% of AKI cases occurring in women with severe disease. Primigravidas had a greater incidence of AKI than multigravidas (63.4% vs. 36.6%), although the difference was not statistically significant (p = 0.081). The incidence of AKI did not significantly correlate with age. Conclusion: AKI is a common and serious complication in pre-eclamptic pregnancies, especially in cases with severe disease. Early detection and close monitoring of renal function in such patients are crucial to prevent long-term renal consequences and improve maternal outcomes. Keywords: Pre-eclampsia, Acute Kidney Injury, Pregnancy Complications, Maternal Outcomes.